ANALISIS HIMBAUAN, PEMERIKSAAN, DAN TINDAKAN PENAGIHAN AKTIF TERHADAP REALISASI PENERIMAAN LIMA KLASIFIKASI LAPANGAN USAHA (KLU) DOMINAN (STUDI KASUS KPP MADYA PEKANBARU) - Iwan Kristoni Napitupulu; Zirman '; Nur Azlina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this research was to find out whether there is or not influence of tax revenue for 5 Dominant KLU’s in Pekanbaru Middle Tax Office (KPP Madya Pekanbaru). This research only focuses on extra-efforts in the tax collection activity, including Advise Letters, Comprehensive Tax Audits, and Collection Activity for Tax Assessment Letters. Thus, tax Revenuefor 5 Dominant Classificatons by Business (KLU’s)that examined, emphasized on the Percentage. Samples that are used in this study is devoted only to the data time series, in the period of 2009 to 2012. By using statistical technique, this research uses multiple linear regression analysis method to answer the hypothesis. Tests carried out simultaneously (F-test) and partially (statistical t-test) with degree of significance (α) = 5%. Analiyzing data use statistical data processing softwares. These result indicate that extra-effort activity, including Advise Letters, Comprehensive Tax Audits, and Collection Activity for Tax Assessment Lettersare significantly affect the percentage of tax Revenuefor 5 Dominant Classification by Business(KLU’s)simultaneously. But, only Collection Activity for Tax Assessment Lettersdoes not affect partially, while two other variables does (Advise Letters, Comprehensive Tax Audits).Keywords : Advise Letters, ComprehensiveTax Audits,Collection Activity for Tax Assessment Letters,Tax Collection Activity, Classification by Business,Tax Revenue of 5 Dominant Classification by Business (KLU’s).